Phenological Characteristics, Distinctness, Uniformity, and Morphological Stability of Potential Genotypes of Upland Rice - Lailatul Badriyah; Dewi Nawank Sary; Thoriq Ahmad Syauqy; Ricoh Darisman Sihombing; Eries Dyah Mustikarini; Gigih Ibnu Prayoga; Ratna Santi; Budi Waluyo (Nusantara Science and Technology Proceedings, 2022)
Every cultivar has characteristics that distinguish it from another cultivar. As opposed to within the cultivar it is required to be uniform and not indicate variations due to segregation. Knowledge of the characteristics of local rice and high-yielding cultivar will be more advantageous if it is supported by knowledge of the morphological changes of plant parts at each stage of growth. This study was conducted to determine the distinctness, uniformity, and stability of 10 potential upland rice genotypes and obtain information about growth stages based on phenology. The research was conducted based on an experimental study using a randomized block design with three replications. Observation of rice genotype characteristics was carried out based on the phenological measurement guide from the Biologische Bundesanstalt, bundessortenamt und CHemische Industrie (BBCH) for rice, and the DUS characterization guide from UPOV. The results showed that the growth stages of 10 rice genotypes consisted of 10 primary growth phases and there are variations in phenological phases in each genotype. Morphological characterization showed that 10 genotypes had a uniform and stable morphology and were grouped into 2 clusters. Cluster 1 consisting of G1, G2, G3, G4, G5, G8, and G10. Cluster 2 consists of G6, G7, and G9. The phenology of rice and morphological differences indicate variations in the genetic potential that each genotype possesses. The timing of morphological and agronomic observations of rice can be determined using the information on plant phenology.